How much is too much? Alcohol consumption and related harm in the Northern Territory - Skov, S.; Chikritzhs, Tanya; Li, S.; Pircher, S.; Whetton, S. (Australasian Medical Publishing Company Pty. Ltd., 2010)
Objective: To present recent estimates of alcohol consumption and its impact on the health of people in the Northern Territory, and to draw comparisons with Australia as a whole. Design, setting and participants: Descriptive study of alcohol consumption in the NT population, based on sales data and self-report surveys, and alcohol-attributable deaths and hospitalisations among people in the NT in the 2004-05 and 2005-06 financial years using population alcohol-attributable fractions specific to the NT. Main outcome measures: Per capita consumption of pure alcohol, self-reported level of consumption, and age-standardised rates of death and hospitalisation attributable to alcohol.Results: Apparent per capita consumption of pure alcohol for both Aboriginal and non-Aboriginal populations in the NT has been about 14 litres or more per year for many years, about 50% higher than for Australia as a whole. We estimated that there were 120 and 119 alcohol-attributable deaths in the NT in 2004-05 and 2005-06, respectively, at corresponding age-standardised rates of 7.2 and 7.8 per 10000 adult population. Alcohol-attributable deaths occur in the NT at about 3.5 times the rate they do in Australia generally; rates in non-Aboriginal people were about double the national rate, while they were 9-10 times higher in Aboriginal people. There were 2319 and 2544 alcohol-attributable hospitalisations in the NT in 2004-05 and 2005-06, respectively, at corresponding rates of 146.6 and 157.7 per 10000 population (more than twice the national rate). Conclusion: In recent years, alcohol consumption and consequent alcohol-attributable deaths and hospitalisations for both Aboriginal and non-Aboriginal people in the NT have occurred at levels far higher than elsewhere in Australia.